Pelatihan Mengenali Emosi Marah Bagi Siswa SMP: Training in Recognizing Angry Emotions for Junior High School Students - Fatchurahman, M (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
As social beings, humans always interact with each other, this is what is always done by every individual. In interacting emotions always appear in someone's, then bring up an attitude and mind to act according to his circumstances. The ability to act then raises an emotional expression. One of them is the expression of angry emotions, this is one of the problems that arise in every teenager (student). This training took place in MuhammadiyahYunior High School Palangkaraya on the grounds of the results of observations and interviews from class teachers and school counselors, based on the results of a questionnaire about the knowledge of angry emotions in pretest is in a low category, no similar training had been conducted at school. The results of this training activity show that there is an increase in the average value of students' understanding of recognizing angry emotions. This means the pretest score is 91.8 (medium category) and the posttest average is 127.28 (high category).